2018
DOI: 10.1177/1098612x18774437
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of an appeasing pheromone diffuser product vs placebo for management of feline aggression in multi-cat households: a pilot study

Abstract: Objectives Aggression and social tension among housemate cats is common and puts cats at risk of injury or relinquishment. The aim of this study was to evaluate the effectiveness of a new pheromone product in reducing aggression between housemate cats. Methods A new pheromone product (Feliway Friends) containing a proprietary cat-appeasing pheromone was evaluated for efficacy in reducing aggression between housemate cats via a randomized, double-blind, placebo-controlled pilot trial of 45 multi-cat households … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
5

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 21 publications
(37 reference statements)
0
23
0
5
Order By: Relevance
“…19 For cats that are showing agonistic interactions, whether covert or overt, a synthetic analogue of feline appeasing pheromone -Feliway MultiCat (USA) or Feliway Friends (Europe) (Ceva) -may diminish reactivity and promote calmer behaviors. 20 See article in Part 2 on pheromone therapy for further information.…”
Section: Pheromone Therapymentioning
confidence: 99%
“…19 For cats that are showing agonistic interactions, whether covert or overt, a synthetic analogue of feline appeasing pheromone -Feliway MultiCat (USA) or Feliway Friends (Europe) (Ceva) -may diminish reactivity and promote calmer behaviors. 20 See article in Part 2 on pheromone therapy for further information.…”
Section: Pheromone Therapymentioning
confidence: 99%
“…On the basis of ligand-binding experiments, using the displacement of a fluorescent probe, and in silico docking simulations, we have shown that a recombinant form of Fel d 1 binds with good affinities some fatty acids and steroids, the best ligands being lauric acid and androstenone (Kd = 2.6 and 2.4 µ M, respectively). Lauric acid is a component of the mixture of fatty acids described as the cat appeasing pheromone having effects on cats' social interactions [36,37], together with oleic, linoleic, and myristic acids, which also showed some affinity to rFel d 1. Androstenone is a volatile steroid pheromone found in high concentrations in the saliva of male pigs and triggers attraction/standing responses in estrous females [43].…”
Section: Discussionmentioning
confidence: 99%
“…The feline facial pheromone F3 has been shown to promote calmness and reduce stress with its related undesirable consequences in cats, such as urine spraying and marking behavior [32][33][34][35]. The maternal cat appeasing pheromone has been shown to have appeasing effects and to facilitate social interactions in cats [36,37]. We have also tested some steroids since several secretoglobins have been experimentally shown to bind steroid hormones, including pig pheromaxein, rabbit uteroglobin, mouse salivary ABP, and rat prostatein [19,[38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…A utilização de análogos sintéticos pode ser feita para situações estressantes ou como parte de terapia comportamental, podendo ser 'spray' ou difusor (ATKINSON, 2018c). O uso de feromônios sintéticos em lares com muitos gatos pode reduzir conflitos e aumentar a sensação de bemestar dos animais (DEPORTER et al, 2018).…”
Section: Tabela 3 Acertos E Erros Na Categoria "Ambienteunclassified